Exploring the potential of taurolidine in inducing mobilization and detachment of colon cancer cells: a preliminary in-vitro study - Agata Mikolajczyk; Veria Khosrawipour; Hien Lau; Shiri Li; Pawel Migdal; Maya Karine Labbé; Wojciech Kielan; Jakub Nicpon; Sven Stieglitz; Tanja Khosrawipour (BMC, 2022)
Abstract Background Recently, taurolidine has been intensively studied on a variety of in-vitro cancer cell-lines and first data exhibit encouraging antitumoral effects. While the clinical use of taurolidine is considered, some studies with in-vivo experiments contradict this beneficial effect and even indicate advanced cancer growth. The aim of this study is to further investigate this paradox in-vivo effect by taurolidine and closely analyze the interaction of cancer cells with the surrounding environment following taurolidine exposure. Methods HT-29 (ATCC® HTB-38™) cells were treated with taurolidine at different concentrations and oxaliplatin using an in-vitro model. Morphological changes with respect to increasing taurolidine dosage were visualized and monitored using electron microscopy. Cytotoxicity of the agents as well as extent of cellular detachment by mechanical stress was measured for each substance using a colorimetric MTS assay. Results Both taurolidine and oxaliplatin exhibit cell toxicity on colon cancer cells. Taurolidine reshapes colon cancer cells from round into spheric cells and further induces cluster formation. When exposed to mechanical stress, taurolidine significantly enhances detachment of adherent colon carcinoma cells compared to the control (p < 0.05) and the oxaliplatin group (p < 0.05). This effect is dose dependent. Conclusions Beside its cytotoxic effects, taurolidine could also change mechanical interactions of cancer cells with their environment. Local cancer cell conglomerates could be mechanically mobilized and may cause metastatic growth further downstream. The significance of changes in cellular morphology caused by taurolidine as well as its interaction with the microenvironment must be further addressed in clinical cancer therapies. Further clinical studies are needed to evaluate both the safety and efficacy of taurolidine for the treatment of peritoneal surface malignancies.